LARGE IGNEOUS PROVINCES AND GIANT DIKE SWARMS: PROXIES FOR SUPERCONTINENT CYCLICITY AND MANTLE CONVECTION - Yale L.B.; Carpenter S.J. (My University, 1998)
The temporal distribution of large igneous provinces (LIPs) and giant dike swarms (GDS) indicates that both occur periodically and are the result of insulation of the mantle following supercontinent assembly. These data define seven possible supercontinent events since 3.0 Ga. The periodicity of these events (300 to 500 Myr) is consistent with previous estimates of mantle and supercontinent cycling rates. The Mackenzie Dike Swarm (1267 Ma) and the Siberian Traps (250 Ma) are synchronous with two dramatic increases in the rate of GDS production. These events define three episodes of mantle activity since 3.0 Ga. A 475 million year gap in the LIP record occurs during a time of relatively dispersed continents between ∼725 and 250 Ma. This `LIP gap' coincides with a period of Earth history characterized by marine oxygen, carbon, strontium, and sulfur isotope ratios indicative of relatively small mantle fluxes.